Theoretical and Methodological Provisions of the Index of Economic Stability of Countries - Davoyan, Samson; Asatryan, Vahe; Shakhanumyan, Svetlana (Bulletin of Yerevan University G: Economics, 2024)
Each institution of a complex economic system, as a matter of fact, has its effect on reducing or increasing the country's economic stability. When we look at the global economy, these various institutions, under the influence of random or non-random phenomena, continuously change the nature of their interactions, changing also the level of global economic stability. Based on the importance of economic stability, it is necessary to highlight the factors in the sphere of influence of which economic stability has a positive effect on various infrastructures of countries.The article discusses the current problems of economic stability in the 25 countries of the European Union. To solve this complex problem, econometric methods are used; in particular, correlation-regression analysis was carried out with the help of the EViews software package. The obtained results show that in order to ensure economic stability in each country, it is necessary to pay attention to the levels of such indices as the index of global innovation, the index of economic complexity, the index of human potential development, the index of quality infrastructure. As a result of our calculations, it was found that in order to ensure the economic stability of each country of the European Union, it is necessary to implement reforms in various economic directions, which are presented in our research.
Keywords: economic stability; competitiveness; innovation; human development; economic development; sustainable development goals; global peace index